Of Ruskinian Topography: Visible and Legible Salience in Modern Painters - Laurence Roussillon-Constanty (Revue de Géographie Alpine)
As contemporary critics have shown, John Ruskin’s lifelong interest in geology not only provided him with a unique understanding of the mountain as a painting subject but also allowed him to develop an idiosyncratic theory of perception where movement and salience prevail – a theory he then applied to his often memorable prose. At first sight, salience is one feature of landscape that one can easily visually apprehend but much less easily account for in prose writing. However, recent research in linguistics may offer a new model for investigations and the means to identify recurrent patterns serving to highlight the transaction from the visual to the verbal and better qualify the writer’s “word painting”. More specifically, Frédéric Landragin’s investigations on the relation between linguistic and visual salience may allow us to explore Ruskin’s prose further and see how the visual salience he noted in painting carries over in his own writing. Applying the salience model to Ruskin’s prose might therefore prove a new way to uncover some of the more elusive and distinctive features of his writing.